2015
DOI: 10.1080/13607863.2015.1055552
|View full text |Cite
|
Sign up to set email alerts
|

Suicide rates in five-year age-bands after the age of 60 years: the international landscape

Abstract: The overall global suicide rates for each of the eight five-year age-bands are sufficiently large for them to constitute a public health concern. This is especially important given the ongoing rise in the elderly population size and the paucity of data on risk and protective factors for suicide in the five-year age-bands after the age of 60 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
87
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 28 publications
2
87
0
3
Order By: Relevance
“…1 Self-harm may be direct, resulting in immediate pain, injury, or death (eg, overdose) or indirect, which over time may cause harm or death (eg, refusing to eat or drink). 1 Self-harm may be direct, resulting in immediate pain, injury, or death (eg, overdose) or indirect, which over time may cause harm or death (eg, refusing to eat or drink).…”
Section: Introductionmentioning
confidence: 99%
“…1 Self-harm may be direct, resulting in immediate pain, injury, or death (eg, overdose) or indirect, which over time may cause harm or death (eg, refusing to eat or drink). 1 Self-harm may be direct, resulting in immediate pain, injury, or death (eg, overdose) or indirect, which over time may cause harm or death (eg, refusing to eat or drink).…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of people aged 65 years or older exceeded 7% of the total population in Korea in 2000, reaching 13.1% in 2015, and is expected to reach 40% by 2060. Population aging and the rate of suicide among the elderly population are closely associated, and it is predicted that suicide among the elderly will become an important social issue in the future 3) . Although the rate of suicide has been decreasing since 2010, it was 55.5 suicides/100,000 persons in 2014, and remains high 1) .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we found that the crude suicide rate between 2007 and 2013 reached its highest level in those aged ≥75 years, with the highest rates in 2013 compared with 2007 (in 2007, the rates were 4.65 per 100 000 in those aged 65–69 years, 4.36 in those aged 70–74 years and 6.68 in those aged ≥75 years; in 2013, these rates were 5.23, 5.37 and 7.91, respectively). Other studies have shown that the suicide rate has increased with the age, reaching its highest rate in those aged 85–90 years …”
Section: Discussionmentioning
confidence: 99%
“…In many societies, the highest rate of completed suicides is among individuals aged ≥70 years. Suicide rates reportedly increase in individuals aged >65 years, and reach the highest rate at 85–90 years . It has also been reported that the causes and methods of suicide differ between younger and older populations .…”
Section: Introductionmentioning
confidence: 99%